2012
DOI: 10.1002/jgm.1633
|View full text |Cite
|
Sign up to set email alerts
|

A syringe‐focused ultrasound device for simultaneous injection of DNA and gene transfer

Abstract: This new technique provides a simple, safe and efficient nonviral gene delivery approach in skeletal muscle and shows promising applications for gene therapy of human disease, such as Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…These issues may have been due to the defect of animal tolerance of APP/PS1 AD mice or very quick progression of AD pathology in the late stage of the disease, since we have previously shown that US-mediated hNEP gene transfer in vivo is safe in healthy mice and does not induce any complications. 30 Taken together, our nonviral hNEP delivery system via US combined with microbubbles may represent a potential approach for AD therapy. However, the half-life of NEP in vivo needs to be measured periodically over time in future studies.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…These issues may have been due to the defect of animal tolerance of APP/PS1 AD mice or very quick progression of AD pathology in the late stage of the disease, since we have previously shown that US-mediated hNEP gene transfer in vivo is safe in healthy mice and does not induce any complications. 30 Taken together, our nonviral hNEP delivery system via US combined with microbubbles may represent a potential approach for AD therapy. However, the half-life of NEP in vivo needs to be measured periodically over time in future studies.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, this finding also provided a possibility for NEP plasmid injected into peripheral skeletal muscle to be transferred to the brain for AD therapy. 30 Importantly, viral vectors for NEP gene delivery in vivo or in vitro in AD models may be associated with complications that would prevent the use of such a therapeutic strategy in humans. Thus, an efficient and safe NEP delivery system in vivo needs to be established for AD gene therapy in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this should be further clarified in an AD mouse model. Similarly, in another study that used focused ultrasound to introduce hNEP plasmid into the hindlimb of mice, hNEP protein in the skeletal muscle, brain tissue, and blood were detected by Western blotting and enzyme‐linked immunosorbent assay after 7, 14, and 30 days, and Evans blue staining of the injected muscle revealed only minor damage compared with conventional ultrasound transfection, and the injured tissue can recover over time (Li et al, ). These results demonstrate that nonviral methods are generally safer and more efficient for NEP delivery and may be adopted as a standard approach in AD therapy.…”
Section: Nonviral Delivery Of Nepmentioning
confidence: 96%